PENDIDIKAN POLITIK DALAM MENINGKATKAN PARTISIPASI PEMILIH OLEH KPU PROVINSI RIAU JELANG PEMILU 2024 - Alexsander Yandra; Sudaryanto Sudaryanto; Bela Sintiya; Arizal Arizal; Dian Rianita (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2023)
This study discusses Political Education in Increasing Voter Participation by the KPU of Riau Province Ahead of the 2024 Election. The theory used is Ruslan's theory in Prof. Dr. M. Amien Rais, M.A. who put forward several variables, namely the ideological function, the development function, the distribution function, the reward function. While this research is a qualitative research with a descriptive design. The results of this study are that the Riau Province KPU carries out various programs and activities to increase voter participation in the upcoming 2024 elections, the forms of programs and activities carried out are, political education, election outreach and discussions held with participants and other election organizers such as the voters, security forces and other organizers and throughout the process of the election stages that have been carried out well and no election violations have been found by election participants. However, besides that, there are currently obstacles to the Riau Province KPU in increasing voter participation, including the existence of a legal vacuum that requires the KPU to carry out outreach, political education and voter participation in elections. There is a blockage in executive power, the executive's performance is still barren, and it is burdened with the politics of accommodation in carrying out its role. Citizens who do not exercise their right to vote are higher because they do not want to be mobilized compared to those who exercise their right to vote